Instantaneous Rock Blasting Wave and Its Microscopic Characteristics during Interaction with Concrete - Shaoqin Huang; Lifeng Luan; Wanli Xing; Qunyi Liu (Shock and Vibration)
This paper uses improved technology for dynamic strain measurement to investigate the dynamic strain signals of blasting wave action tested in the range of 8–16 cm from the central blast. Based on the blasting mechanism and on the analysis of signal characteristics, blasting waves are recognized and divided into three zones, namely, shock wave zone, stress wave zone, and gas-expanding zone. This paper studies the relationships between stress, strain, and time of every zone. The tensile and compressive stresses of stress wave are considered. After the blasting test, four cracks from the borehole center toward the minimum burden appear at the model surface. The relationship between blasting wave and concrete damage is analyzed.